(untitled) (Singapore [etc.], 1997)
Offers a taste of the diverse management and economic climate in Asia by placing a magnifying glass over the economies of Asia. It first develops a framework for understanding business strategy, then provides a detailed profile of Asian countries with spotlights on their business characteristics and how that affects the implementation of strategy.
Keywords: Corporations; Tập đoàn; Asia